First Report of the Joint Exposure to Glyphosate and Glufosinate of a Male Population in the Province of Córdoba (Argentina) - Filippi, Iohanna (2023)
Despite potential health implications, data on the presence of Glyphosate (GLY) and other non-GLY herbicides in human matrices remain scarce. This study aimed to develop a simple and cost-effective methodology for detecting and quantifying GLY, its primary biodegradation product; aminomethylphosphonic acid (AMPA); and glufosinate (GLU) in plasma and urine of environmentally and occupationally exposed populations from the province of Córdoba (Argentina). Different alternatives of pre-treatment, derivatization with FMOC-Cl, solid phase extraction, and final sample conditioning steps were evaluated to improve the quantification of the herbicides by a high-performance liquid chromatography system coupled to a triple-quadrupole mass spectrometer. Recoveries ranged from 39 to 84% in both matrices, while limits of quantification were 3, 1, and 0.3 ng/mL and 3.6, 5.1, and 0.3 ng/mL for AMPA, GLY, and GLU in plasma and urine, respectively. In plasma samples, GLY was the most frequently detected analyte (32%), followed by GLU (10%). In urine samples, GLU was the most frequently detected herbicide (13%), followed by GLY (6%). No differences between group or matrix correlations were found. This study is the first report of GLU in human biological matrices and should be used to establish baseline values for future surveillance systems.